PENGEMBANGAN BAHAN AJAR BERBASIS VIDEO PEMBELAJARAN DALAM PEMAHAMAN SISWA PADA MATA PELAJARAN FIQIH - Yeni Apriliyanti; Jasiah Jasiah (JOURNAL SAINS STUDENT RESEARCH, 2025)
This article aims to develop video-based teaching materials for learning in the fiqh teaching module. With the rapid development of technology, the use of video as a learning medium provides great potential in increasing students' understanding of fiqh material which is often considered complex. Through observations and interviews with students and teachers in fiqh subjects, it turns out that students are more enthusiastic about learning with learning videos, students admit that they are not bored and are happy with learning video lessons. The research method used is research and development (R&D) with a spiral model (planning, risk analysis, product development, evaluation). The results of this research show that video-based teaching materials can enrich students' learning experiences and increase their involvement in fiqh learning. The learning videos that are developed can also simplify the explanation of material that is difficult to understand, as well as provide a different experience in teaching techniques. Therefore, the application of video-based teaching materials is highly recommended in developing fiqh teaching modules to increase learning effectiveness.